Pengaruh Karakteristik Internal Penyuluh Swadaya Terhadap Efektivitas Temu Teknis Online Teknologi Tanaman Obat di Sumatera Barat: Lailatul Rahmi, Rifda Roswita, Rustam, Firmansyah Aznur - Lailatul Rahmi (Sumber Penyuluhan Pertanian Indonesia, 2023)
Biopharmaceutical crop production in Indonesia from 2019 until 2021 has increased greatly. Opportunities to increase the potential of medicinal plants can still be done by implementing new technologies to farmers through training/assistance provided by agricultural extension workers through online technical meeting. To determine the influence of the internal characteristics of independent agricultural extension workers on the effectiveness of technical meetings of medicinal plant cultivation and processing technology carried out online, for the technology of cultivation and processing of medicinal plants, this research was conducted. This research was carried out on Independent Agricultural Extension Officers from Payakumbuh City, and Independent Agricultural Extension Workers from Limapuluh Kota Regency. with a total of 32 participants who took part in a technical meeting at the ITC Building / Livestock Training and Keswan Of the Livestock and Animal Health Office of West Sumatra Province, Ibuh Village, West Payakumbuh District, Payakumbuh City on November 23, 2021. The research was conducted through a survey before and after the technical meeting, using a list of questions that had been prepared.This research method uses a quantitative approach supported by qualitative data. The method of data collection uses questionnaires, the data collected are in the form of respondents' characteristics, test results before and after the delivery of the material and farmers' perceptions of the effectiveness of organizing technical meetings. The analysis used in this study is a simple linear regression test. The internal characteristics of independent agricultural extension workers that have a real effect on the effectiveness of online technical meetings are age.